PENYIDIKAN TINDAK PIDANA PEMALSUAN SURAT KETERANGAN TANAH DAN SURAT KETERANGAN GANTI RUGI YANG DILAKUKAN OLEH CAMAT DI KEPOLISIAN RESOR KOTA DUMAI - Hutabalian, Malvin; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Advancement of the economy of a region will always be accompanied with the increase of various kinds of criminal acts in the region, this too has happened in the region laws City Police Dumai where Kota Dumai turns menyisahkan 2 issue of the crime of forgery that occurred in 2012 and 2013, but the year 2013 forgery case has not been resolved completely and was still under investigation by the police.In the process of investigation by the police on criminal acts dumai town this falsification experience various inhibiting factors in the investigation, one of which is the testimony of witnesses who where witnesses can not provide detailed information and explanations seem convoluted and difficult to understand. While witness testimony is one tool in exposing evidence of a crime. Therefore the investigation of criminal cases of forgery that occurred in 2013 are not resolved completely.From the research the problems faced by the Police Dumai can be concluded, namely: First, the investigation conducted by the Police Dumai against fraud statement on land and compensation. Second, inhibiting factors experienced by the investigator to conduct the investigation of forgery and not maximal performance of police officers. Third, efforts made to overcome the problems in the investigation of criminal cases of forgery statement on land and compensation by giving socialization to the community so that law-abiding are not afraid to be a witness if the look and feel of offense happened.Keywords: Process-Crime Investigation-Counterfeiting-Mail